Clinical Implications of Inflammation in Acute Myeloid Leukemia - Récher, Christian (Frontiers in Oncology, 2021)
Recent advances in the description of the tumor microenvironment of acute myeloid leukemia, including the comprehensive analysis of the leukemic stem cell niche and clonal evolution, indicate that inflammation may play a major role in many aspects of AML such as disease progression, chemoresistance, and myelosuppression. Studies on the mechanisms of resistance to chemotherapy or tyrosine kinase inhibitors along with high-throughput drug screening have underpinned the potential role of glucocorticoids in this disease classically described as steroid-resistant in contrast to acute lymphoblastic leukemia. Moreover, some mutated oncogenes such as RUNX1, NPM1 or SRSF2 transcriptionally modulate cell state in a manner that primes leukemic cells for glucocorticoid sensitivity. In clinical practice, inflammatory markers such as serum ferritin or IL-6 have a strong prognostic impact and may directly affect disease progression, whereas interesting preliminary data suggested that dexamethasone may improve the outcome for AML patients with a high white blood cell count, which paves the way to develop prospective clinical trials that evaluate the role of glucocorticoids in AML.